Az imádság mint feldolgozás: Politikai krízisek és természeti csapások értelmezése a kora újkortól a 20. századig - Fazakas, Gergely Tamás (Studia Litteraria, 2011)
While we can consider the difficulties of using the cultural trauma theories for texts produced before the nineteenth century, and several hurried interpretation resulted misapplication of these approaches to early modern history and litearature, in this essay I intend to introduce a new British research project, and try to frame by cultural trauma theory and its critics. British state prayers, fasts and thankgivings (1540s–1940s) is managed by a research group of the University of Durham, United Kingdom. Participants investigate the tradition of national state prayers, fast or humiliation days, thanksgiving days and national days of prayer.Special church services were organised and prayers were read in all parish of England as well as Scotland, Ireland and Wales. In particular dates or periods (epidemics, war, famine, rebellion, good/bad harvests, royal births etc.) the King/Queen, the government, and the archbishop of Canterbury, or other church leaders officially ordered special acts of national worship. Prayers and sermons presented the nation as a sinful community, and urged them to practice repentance, because it was thought that calamities will come to an end only, if people convert themselves to God. The research group in Durham is investigating when and how these occasions ordered (by proclamation, privy council order, or by royal request).From the aspect of cultural trauma theory I compare several official religious interpretations of particular events, and try to highlight the pressure of the authority (monarchy, government) on their political and/or religious counterparts on the one hand, and the battles for special events of national memory on the other hand. Cultural trauma theory offers some formulations for explaining the ’working through’ of political crises and natural calamities from sixteenth to twentieth century, and show us how to consider consequences of devastating loss and pain of a community, whether national and/or religious.Interpretation of these crises as prompt and continuous reaction to a traditional, Biblical language, may help the community to explain the cathastrophic events, and to develop a necessary condition for working through. This means that there is no latency, which might causes and signs cultural trauma.Using trauma theories and its critics, I try to find possibilities to transform this international research for a future Hungarian investigation.